M10, a Myricetin-3-O-b-D-Lactose Sodium Salt, Prevents Ulcerative Colitis Through Inhibiting Necroptosis in Mice - Zhou, Xiao-Ling; Yang, Juan; Qu, Xian-Jun; Meng, Jian; Miao, Rong-Rong; Cui, Shu-Xiang (Frontiers in Pharmacology, 2020)
Background: M10 is a derivative of Myricetin by adding a hydrophilic glycosylation group. Our previous study revealed that M10 by oral administration prevented colitis-associated colonic cancer (CAC) through attenuating endoplasmic reticulum stress in mice. In current study, we evaluated the inhibitory effects of M10 on chronic ulcerative colitis in mice model, the mechanism of M10 in preventing colitis was further investigated. Methods: Mice model of ulcerative colitis was induced by continuous oral dextran sodium sulfate (DSS). M10 was given gavage once a day for 12 consecutive weeks. Disease activity index (DAI) was recorded by analyzing the symptoms of colitis. Intestinal barrier was analyzed by the Immunoﬂuorescence staining assay. The structures of microvilli of intestinal epithelial cells was checked under Transmission electron microscopy (TEM). TEM assay was also performed to determine the formation of necroptosis in the colonic epithelium with ulcerative colitis. We performed Western blotting assay to analyze the IL-6 and NF-κB pathways, as well as the cytokine cascades related to TNF-α signaling pathway during necroptosis. Results: M10 by oral administration demonstrated a prevention of ulcerative colitis, showing a significant decrease of DAI as compared to the model mice. Pathological analysis indicated that M10 attenuated the degree of colonic inflammation in colonic tissues. M10 restored the structures of intestinal barrier damaged by DSS. M10 prevented the activation of IL-6/NF-κB and TNF-α pathways during colitis. Further, M10 prevented necroptosis in the inﬂamed colonic mucosal cells through down-regulating the TNF-α pathway. Importantly, M10 demonstrated higher activities in preventing ulcerative colitis than Myricetin and control drug Mesalazine. Conclusions: Myricetin derivative M10 prevents chronic ulcerative colitis through inhibiting necroptosis. M10 could be developed as a promising drug for the treatment of chronic ulcerative colitis.